i would say D) 12 is your answer
Answer:
The solution of given equation is ( - 1 + 2 i ) , ( - 1 - 2 i )
Step-by-step explanation:
Given equation as :
3 x² + 6 x +15 = 0
The value of x fro the quadratic equation a x² + b x + c = 0 is obtained as
x =
So , from given eq , the value of x is now obtain as
x =
Or, x =
Or, x =
∴ x = ( - 1 + 2 i ) , ( - 1 - 2 i )
Hence The solution of given equation is ( - 1 + 2 i ) , ( - 1 - 2 i ) Answer
Answer:
x=y/4
Step-by-step explanation:
Simply divide by 4 to get x by itself
Answer:
2.57 x 10^1
is the scientific notation of 25.7
Answer:
10.7
Step-by-step explanation: